О так называемых «синтаксических балтизмах» - Прохорова, С. М. (Baltistica, 1988)
TOWARDS THE PROBLEM OF THE SO-CALLED “SYNTACTIC BALTICISMS”The article presents the results of the investigation of the so-called “syntactic balticisms” and determines the role of the Baltic substratum in some Slavic territories. The “syntactic balticisms” is shown to be a heterogeneous phenomenon. Three types of syntactic balticisms are singled out: (1) the balticisms proper which appeared in certain Slavic territories as a result of direct contacts with Baltic population (mainly as a substratum); (2) Balto-Slavic innovations of wide and limited occurrence the centre of which was located both within the Baltic and the Slavic territories; 3) survival phenomena which remained both in the Baltic and the Slavic territories. The term „balticism“ for the latter can be used but conventionally, because these phenomena can be rooted back in the ancient times and can be common not only to the Baltic and the Slavic languages (while they are widely spread in the Baltic territories).
Keywords: sintaksiniai baltizmai